AB1000 Acute Osteoarticular Infections in Children in a Tertiary Hospital: Our Experience Across 5 Years. (9th June 2015) - Sánchez-Moreno, P.; Ardanuy-Pizarro, A.V.; Navarro, L.; Melόn, M.; Falcόn-Neyra, M.D.; Camacho-Lovillo, M.
Abstract : Background: Acute osteoarticular infections (AOI) are potentially severe disease. A consensus document about them has been recently published in our country. The aim of this study was to evaluate the epidemiology, etiology, diagnostic approach and treatment of AOI in our hospital. Methods: Retrospective descriptive study of children (<14 years) with AOI attended from January 2009 to June 2014 at a tertiary hospital. Results: 117 cases were reviewed. 78 cases (66.6%) were septic arthritis (SA), 25 cases (21.3%) were osteomyelitis (OM) and 14 (11.9%) osteoarthritis (OA). SA was most frequent in females (54%) whereas OM in males (60%). Median age at diagnostic was higher in OM (47 vs 31 months in SA). Fever was less common in SA (79% vs 84% in OM). Pain was the most frequent symptom in OM (68%) and swelling in SA (41%). Previous risk factors were found more frequently in SA (51% vs 36% in OM), being the most common trauma, and highlighting the common cold in SA. Knee was the most common location (59%) in SA whereas femur and tarsus (both 32%) in MO. Median CRP on admission was 49, 7 mg/L in SA and 56, 2mg/L in OM. Initial ESR determination was uncommon (13%). Conventional X-Ray were performed in a significant percentage of patients, having low yield for both diagnosis. 92% of US performed in SA were compatible against 75% of the OM. MRI and bone scintigraphy had the highest yield for SA and OM diagnosis (100%). MRI was done in 88% of OM vs 15% of SA whereas scintigraphy was done in 88% of OM vs 7% of SA. Arthrocentesis was performed in 77% of SA, joint fluid was obtained in 73% and 24.5% of fluid cultures were positive. Blood culture was conducted in 71% of patients (36% positive in SA; 32% in OM). S. Aureus was the most frequent bacteria isolated in joint fluid and blood cultures. All the patients were admitted. Most children received intravenous antibiotic treatment with cefotaxime and cloxacillin, for a median of 10.45 (±5) days for OM and 7.7 (±4.5) days for SA. Cefadroxile was the most common oral antibiotic (85%). Total treatment duration was 27 (±16) days for OM and 26.1 (±16) days for SA. 16% of children with OM and 27% with SA underwent surgery. Only 5% of SA had complications or sequels. Conclusions: The characteristics of our patients were similar to those published to date. Understanding the epidemiology, etiology and therapeutic approach of our series will allow us to compare it with those of a prospective multicenter study that will be developed following the national consensus publication. References: Saavedra-Lozano J, et al. An Pediatr (Barc). 2014. Gutierrez K. Osteomyelitis. 4th ed. Philadelphia: Churchill Livingstone; 2012. p. 469-77 and 77-83. Paakkonen M. Pediatr Clin North Am. 2013;60:425-36. Disclosure of Interest: None declared